Behavior and design for component and system of cold-formed steel roof trusses. (February 2019) - Reda, M.; Sharaf, T.; ElSabbagh, A.; ElGhandour, M.
Abstract: The experimental investigation of the behavior of cold formed steel (CFS) roof trusses does not offer a prior knowledge about either which member will fail first or the capacity of the whole truss. This research aims to investigate the overall behavior of CFS roof trusses using finite element analysis and to predict the failure location in the truss assembly and its cause by calculating the demand to capacity ( D/C ) ratios using Direct Strength Method (DSM) for each component of the truss and compare it with finite element results. Twelve trusses were examined under the same gravity load and boundary conditions to study the effect of span, the truss web pattern, and the cross section type of truss members on the ultimate strength of the truss. Results revealed that for longer spans, Fink truss configuration is better than Howe truss. The member with the maximum D/C ratio will be the first member to fail in FEA, so engineer can use D/C components' ratio instead of FEA to predict the first member to fail, the cause of failure, and truss capacity. The results of D/C ratio values showed that each truss was designed with high efficient critical components and highly variable D/C ratios, which increase the probability of producing an alternative load path to the loads that are carried by the failed truss members. The reliability of truss system is much greater than the reliability of any component as the truss system's D/C ratio calculated from FEA is always less than the maximum component's D/C ratio from the design. Highlights: Increasing the heel thickness in Fink trusses increases the probability of load redistribution mechanism. The designer is able to control the failure location in some cases. In small spans, there is no big difference in capacity between U-shaped and C-stud trusses with both Fink and Howe configuration. The highly variable components' D/C ratios in the truss system increase the probability of producing an alternative load path to the carried loads. The reliability of truss system is much greater than the reliability of any component.